Aetiogical Pattern of Adult Gastric Outlet Obstruction - Ansary, Abdullah Md Abu Ayub; Hossain, Muhammad Mofazzal; Foez, Syed Abul; Talukdar, Md Monoarul Islam; Rahman, Mohammad Moshiur; Hassan, Mehedi; Mohit, Muhammad Tanvir (Journal of Shaheed Suhrawardy Medical College, 2018)
a